Comparison Study of Various Type Artificial Reef Performance in Reducing Wave Height - Rifqi Fauzi, Muhammad Aldhiansyah; Armono, Haryo Dwito; Mustain, Mahmud; Amalia, Aniendhita Rizki (Institut Teknologi Sepuluh Nopember, 2017)
Most fishermen used inappropriate methods to sustain their livelihoods, severely destroying fishery resources. Furthermore, a lack of environmental protection and pollution prevention lead the best coastal and estuarial nurseries to become unhabitable. Several studies have pointed out that fish stocks in coastal waters could be no longer sufficient for the increasing fishing activity and consumption requests. Based on the 1950â€“2006 global statistics conducted by Food andÂ Agriculture Organization of the United Nations (FAO) (2012).Artificial reefs are most often constructed to increase the efficiency of fishery resource harvest (Seaman and Sprague, 1991). In engineering practice, the stability of artificial reefs is an important issue in preventing the failure of reef units due to wave and current actions. Some of the artificial reefs have also been designed to serve as low-crested coastal protection structures (e.g. Dalrymple et al., 1991a; Ranasinghe et al., 2006). One particular advantage of these artificial reefs over the conventional submerged breakwaters is the fact that they are multi-purpose units and can be achieved with more cost-effective materials and environmentally friendly construction processes (Harris, 1995; Buccino et al., 2013). Artificial reef model keep looking for modification to get compatibility and efiiciency as submerged breakwater becauseÂ the feasibility of artificial reefs for coastal protection is typically evaluated based on the percentage of surface wave height reductionWave transformation analysis in artificial reef do with consideration from some non dimensional variables. Wave transmission process defined with ratio betwwen transmission wave height and incoming wave heightThis research compares 5 types of Artificial reef in numeric model. There are hexareef, bottle reef, star reef, seadome and cube reef. They are tested with Indonesian wave steepness which has value between 0,0013 and 0,012.